Acute visual loss and intraocular hemorrhages associated with endoscopic spinal surgery - Marilita M Moschos (Dove Medical Press, 2008)
Marilita M Moschos, Alexandros Rouvas, Alexios Papaspirou, Michael ApostolopoulosDepartment of Ophthalmology, University of Athens, GreecePurpose: To report a case of acute visual loss after endoscopic spinal surgery.Methods: A patient was immediately referred to our department after epidural endoscopy with severe bilateral visual impairment and underwent complete ophthalmologic examination.Results: Visual acuity was decreased in both eyes. Fundus examination revealed the presence of retinal and vitreous hemorrhages bilaterally. Four months later, visual acuity increased and the hemorrhages were remarkably resolved.Conclusion: The present case represents an extremely rare incidence of intraocular hemorrhage following epiduroscopy.Keywords: visual acuity, hemorrhage, intraocular, BCVA